Preparation of stimuli-responsive nanogels based on poly(N, N-diethylaminoethyl methacrylate) by a simple "surfactant-free" methodology. Issue 1 (2nd January 2018) - Manzanares-Guevara, Lizbeth A; Licea-Claverie, Angel; Paraguay-Delgado, Francisco
ABSTRACT: The synthesis of poly(N, N-diethylaminoethyl methacrylate)-core-polyethyleneglycol-shell (PDEAEM-core-PEG-shell) nanogels was achieved by using a "surfactant-free" emulsion polymerization with the aid of commercially available polyethyleneglycol methyl ether methacrylates (PEGMAs) as polymerizable stabilizers. By adjusting the synthetic parameters like the choice of initiator, cross-linker, PEGMA:DEAEM ratio, and molecular weight of PEGMA, a series of core-shell nanogels varying in size (50–350 nm), PDEAEM content, and pH/temperature responsive behavior were obtained in reactions taking only 60 min. The nanogels were used as nanoreactors for the preparation of gold nanoparticles. The PEGylated nanogels have a great potential to be used for diagnosis and therapy.